Tuyển Cộng tác viên Hoc24 nhiệm kì 26 tại đây: https://forms.gle/dK3zGK3LHFrgvTkJ6


Những câu hỏi liên quan
ND
Xem chi tiết
ND
Xem chi tiết
ND
Xem chi tiết
ND
Xem chi tiết
ND
Xem chi tiết
HH
Xem chi tiết
NL
29 tháng 1 2016 lúc 20:55

1/21+1/28+1/36+...+2/x(x+1)=2/9

=>1/3.7+1/4.7+1/4.9+...+2/x.(x+1)=2/9

=>2/2.3.7+2/2.4.7+2/2.4.9+...+2/x.(x+1)=2/9

=>2/6.7+2/7.8+2/8.9+...+2/x.(x+1)=2/9

=>2.(1/6-1/7+1/7-1/8+1/8-1/9+...+1/x-1/x-1)=2/9

=>2.(1/6-1/x+1)=2/9

=>1/6-1/x+1=1/9

=>1/x+1=1/6-1/9

=>1/x+1=1/18

=>x+1=18

=>x=18-1

=>x=17

Bình luận (0)
H24
Xem chi tiết
HY
2 tháng 4 2016 lúc 20:14

Ta có \(\frac{1}{21}+\frac{1}{28}+\frac{1}{36}+....+\frac{2}{x\left(x+1\right)}\)

=\(2\left(\frac{1}{42}+\frac{1}{56}+....+\frac{1}{x\left(x+1\right)}\right)\)

=\(2\left(\frac{1}{6.7}+\frac{1}{7.8}+.....+\frac{1}{x\left(x+1\right)}\right)\)

=\(2\left(\frac{1}{6}-\frac{1}{7}+\frac{1}{7}-\frac{1}{8}+....+\frac{1}{x}-\frac{1}{x+1}\right)\)

=\(2\left(\frac{1}{6}-\frac{1}{x+1}\right)\)

=>\(2\left(\frac{1}{6}-\frac{1}{x+1}\right)=\frac{2}{9}\)

=>\(\frac{1}{6}-\frac{1}{x+1}=\frac{2}{9}:2\)

\(\Rightarrow\frac{1}{x+1}=\frac{1}{6}-\frac{1}{9}\)

\(\Rightarrow\frac{1}{x+1}=\frac{1}{18}\)

=> x+1=18

x=18-1

x=17

Bình luận (0)

2 / 6,7 + 2 / 7.8 + ... + 2 / x (x + 1) = 2/9 Ta có: 1 / x - 1 / (x + 1) = (x + 1 - x) / x (x 1) = 1 / x (x + 1) ⇒ 2 / x (x + 1) = 2 / x - 2 / (x + 1) (*) trở thành: 2/6 - 2/7 + 2/7 - 2/8 + ... + 2 / x - 2 / (x + 1) = 2/9 ⇔ 2/6 - 2 / (x + 1) = 2/9 ⇔ 1/6 - 1 / (x + 1) = 1/9 ⇔ 1 / (x + 1) = 1/18 ⇔ x + 1 = 18 ⇔ x = 17 Đáp số: x = 17

Bình luận (0)
PN
Xem chi tiết
HG
14 tháng 7 2015 lúc 8:45

\(\frac{1}{21}+\frac{1}{28}+\frac{1}{36}+....+\frac{2}{x\left(x+1\right)}=\frac{2}{9}\)

\(\frac{2}{42}+\frac{2}{56}+\frac{2}{72}+....+\frac{2}{x\left(x+1\right)}=\frac{2}{9}\)

2\(\left(\frac{1}{6.7}+\frac{1}{7.8}+\frac{1}{8.9}+....+\frac{1}{x\left(x+1\right)}\right)=\frac{2}{9}\)

\(\frac{1}{6}-\frac{1}{7}+\frac{1}{7}-\frac{1}{8}+\frac{1}{8}-\frac{1}{9}+....+\frac{1}{x}-\frac{1}{x+1}=\frac{2}{9}:2=\frac{1}{9}\)

\(\frac{1}{6}-\frac{1}{x+1}=\frac{1}{9}\)

\(\frac{1}{x+1}=\frac{1}{6}-\frac{1}{9}=\frac{1}{18}\)

=> x+1 =18

=> x = 18 - 1

=> x = 17

Bình luận (0)
DM
Xem chi tiết